Structural, magnetic properties and phase stability of CrAs in the zinc-blende structure: Investigated by first principle calculations and Monte Carlo simulation. (January 2021) - Azouaoui, A.; El haoua, M.; Benzakour, N.; Hourmatallah, A.; Bouslykhane, K.
Abstract: We have employed the first-principles calculations of density functional theory (DFT) using the generalized gradient approximation (GGA) to investigate the structural, magnetic and electronic properties of CrAs of zinc-blende structure (ZB-CrAs). The obtained results show that ZB-CrAs is more stable in the ground state with a ferromagnetic (FM) configuration. Density of States (DOS) calculations show a half-metallic behavior in FM configuration with a magnetic moment of 3 . 00 μ B and metallic behavior in antiferromagnetic (AFM) configuration. Under the pressure, the CrAs undergoes structural and magnetic transitions from a ferromagnetic ZB-CrAs structure to an antiferromagnetic Pnma structure at 5 GPa. The obtained data from DFT calculations are used as input data in Monte Carlo simulation with Potts model and mean field theory to calculate the Curie temperature ( T C ) . The obtained values of Tc by Monte Carlo simulation and mean field theory are well above 400 K. Highlights: Behavior half metallic of CrAs in the ZB Structure in FM. Under the pressure, the CrAs undergoes structural and magnetic transitions from a FM ZB to an AFM Pnma . The T C of CrAs in the ZB is higher than room temperature.